2020
DOI: 10.9734/jalsi/2020/v23i430157
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic Effect of Gamma Radiation on Macro Mutation Spectrums, Effectiveness and Efficiency under M3 Generation in Pea (Pisum sativum L.)

Abstract: Mutation breeding is one of the most reliable techniques in improving crop plants. The study was frequency and spectrum of macro-mutations along with the mutagenic effectiveness and efficiency of different doses of gamma rays in pea variety (Arkel). The irradiated seeds were sown in the M1, M2 generations in their respective control and harvested in bulk to raise the M3 generation (2013-14) in Randomized Block Design with three replications. Screening of the M3 generation revealed that the mutagenic treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Similar to seedling height, the greater the dosage of gamma radiation, the lower the pollen fertility %. This conclusion was already endorsed by a number of studies [37][38][39][40][41][42]. Kumar, et al [38] demonstrated that when dried seeds of pea were irradiated, a 5 kR dosage of gamma rays induced 10.06 percent pollen sterility, while a 40 kR exposure generated 53.12 percent pollen sterility.…”
Section: Plos Onementioning
confidence: 82%
See 1 more Smart Citation
“…Similar to seedling height, the greater the dosage of gamma radiation, the lower the pollen fertility %. This conclusion was already endorsed by a number of studies [37][38][39][40][41][42]. Kumar, et al [38] demonstrated that when dried seeds of pea were irradiated, a 5 kR dosage of gamma rays induced 10.06 percent pollen sterility, while a 40 kR exposure generated 53.12 percent pollen sterility.…”
Section: Plos Onementioning
confidence: 82%
“…This conclusion was already endorsed by a number of studies [ 37 42 ]. Kumar, et al [ 38 ] demonstrated that when dried seeds of pea were irradiated, a 5 kR dosage of gamma rays induced 10.06 percent pollen sterility, while a 40 kR exposure generated 53.12 percent pollen sterility. Additionally, when presoaked seeds were utilized, they observed an increase in pollen sterility.…”
Section: Discussionmentioning
confidence: 99%